Cardiovascular Protection of Nephropathic Male Patients by Oral Food Supplements - Annalisa Noce; Giulia Marrone; Manuela Di Lauro; Silvia Urciuoli; Anna Pietroboni Zaitseva; Georgia Wilson Jones; Nicola Di Daniele; Annalisa Romani (Hindawi-Wiley, 2020)
Nephropathic patients show elevated cardiovascular morbidity and mortality compared to the general population. In order to delve deeper into the understanding of this phenomenon, it is necessary to recognize risk factors that are distinctive to the uremic state, such as oxidative stress and chronic low-grade inflammation. Moreover, gender differences have been reported in nephrology, as it has been observed that chronic kidney disease has higher prevalence in males than in females. The use of an oral food supplement (OFS) containing natural active compounds from Capsicum annuum L., Garcinia cambogia, Centella asiatica L., artichoke, and Aesculus hippocastanum L. which are virtually devoid from side effects, but rich in antioxidant and antiradical properties, could represent a valid therapeutic adjunct in the clinical management of nephropathic patients. Moreover, quantitative analysis performed in vitro on such compounds showed that they expressed good total antioxidant (7.28 gallic acid equivalents) and antiradical activity (above 80%). In this study, 23 male nephropathic patients and 10 age and body composition parameter matched healthy males (control group) were enrolled and took 3 cps/day of OFS for 5 weeks. At the end of the study, the nephropathic patient group showed a statistically significant reduction in the following laboratory parameters: total cholesterol (TC) (p=0.044), atherogenic index TC/high-density lipoprotein cholesterol (p=0.010), inflammatory parameters (C-reactive protein, p=0.048, and erythrocyte sedimentation rate, p=0.019), systolic (p=0.044), and diastolic arterial blood pressure (p=0.003). Regarding body composition, there was an increase in total body water % (p=0.035) with redistribution of extracellular water % (p=0.030) and intracellular water % (p=0.049). In the control group, there was a reduction in fat mass % (p=0.017) and extracellular water % (p=0.047). Therefore, this OFS may represent a valid adjunct therapy to counteract comorbidities related to uremia.